Konsep Tabayun dalam Perspektif Islam sebagai Upaya Menghadapi Hoax - Zulfa Aqila Haq; Cika Nurossobah; Ahmad Sahal Amar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of digital technology has changed the way people receive and share information. Social media makes information spread quickly, but many users often share news without checking its truth first. This situation has caused hoaxes to spread more widely in society. The spread of false information can lead to misunderstandings, social conflict, and decreasing public trust in digital communication. This study discusses the concept of tabayyun in Islam as an effort to respond to hoaxes in the digital era. The research uses a qualitative descriptive method with a literature study approach by collecting data from journals, articles, and islamic sources related to hoaxes and tabayyun. This study found that tabayyun has a important role in encouraging people to verify information before believing or sharing it with others. The values contained in tabayyun also teach honesty, carefulness, and responsibility when communicating, aspecially on social media. Therefore, applying the principle of tabayyun can help reduce the spread of false information and support healthier digital communication in modern society.